1992
DOI: 10.1212/wnl.42.4.770
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors in Alzheimer's disease

Abstract: We investigated potential risk factors for Alzheimer's disease (AD) in a clinicopathologic study of 407 patients with definite AD, 100 non-Alzheimer dementia patients, and 50 normal subjects. The AD patients had more first-degree relatives with dementia than the non-AD dementia group (odds ratio of 1.85, 95% confidence interval of 1.07-3.20) or the normal elderly (odds ratio of 3.60, 95% confidence interval of 1.50-8.64) but did not have significantly more head injuries, medical and psychiatric illnesses, or r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
9

Year Published

1994
1994
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 0 publications
2
22
0
9
Order By: Relevance
“…Putative Risk Factors A variety of risk factors such as old age, family history of dementia in first-degree relatives or apolipoprotein E4 allele have been related to Alzheimer's disease [24] . Other risk factors such as low educational attainment, head trauma, hypertension, type 2 diabetes mellitus, smoking, cerebrovascular and cardiovascular disorders have also been speculated to be related to Alzheimer's disease [25][26][27][28][29][30][31] .…”
Section: Surveymentioning
confidence: 99%
“…Putative Risk Factors A variety of risk factors such as old age, family history of dementia in first-degree relatives or apolipoprotein E4 allele have been related to Alzheimer's disease [24] . Other risk factors such as low educational attainment, head trauma, hypertension, type 2 diabetes mellitus, smoking, cerebrovascular and cardiovascular disorders have also been speculated to be related to Alzheimer's disease [25][26][27][28][29][30][31] .…”
Section: Surveymentioning
confidence: 99%
“…Myocardial in farction (MI) was associated with an increased risk of dementia, when women with and without a history of MI were compared, but did not reach significance for the total sample. Other studies have found no relationship between heart disease and dementia [21][22][23].…”
Section: Introductionmentioning
confidence: 85%
“…Emerson et al [22] found no evidence of car diac abnormalities in a controlled study of dementia patients, and this finding was replicated in a retrospective study of Mendez et al [23], although identification of risk factors in medical history depended on information from family informants. Breteler et al [15] did not consider coronary heart disease in their meta-analysis of risk fac tors in medical history in AD Neuropathological studies provide no evidence of a link between coronary heart disease and dementia.…”
Section: Hypertension Ischaemic Heart Disease and Dementiamentioning
confidence: 92%
See 1 more Smart Citation
“…A number of family studies have confirmed that genetic risk factors play an important role in the aetiology of Alzheimer's disease (AD) (Heston et al, 1981;Heyman et al, 1983;Breitner and Folstein, 1984;Huff et al, 1988;Farrer et al, 1989;Mendez et al, 1992;Korten et al, 1993;Silverman et al, 1994;Heun et al, 2001). Some of these genetic risk factors might also predispose to other physical disorders.…”
Section: Introductionmentioning
confidence: 99%